The Delta Transport Processes Laboratory: a novel laboratory for surface wave-induced currents under rotation - Bayle, Paul; Middelplaats, Lennart; Weststeijn, Cornel; van der Gaag, Pieter; de Gans, Danny; Mol, Jessamy; van't Hof, Stephan; Leenheer, Lars; van Meurs, Jos; Haine, Maarten; Mills-Williams, Rory; Willems, Chantal; et al. (Journal of Coastal and Hydraulic Structures, 2025)
Marine pollution is a major global environmental problem. The transport and dispersion of marine pollution is driven by a wide range of hydrodynamic processes, including wave-induced currents (e.g., Stokes drift) that are generated by free-surface and internal gravity waves in density-stratified fluids. While the (Lagrangian-mean) Stokes drift is known to fundamentally change transport patterns, wave-induced Eulerian-mean currents, such as those generated in the presence of the Coriolis force due to the Earth's rotation, are generally less well understood. To address this, the Delta Transport Processes Laboratory (DTP-Lab), a multi-purpose lab with novel facilities and state-of-the-art equipment, is being constructed in the Hydraulic Engineering Laboratory at TU Delft. The DTP-Lab combines multiple components: a 4.40-m diameter turntable, which can support a (removable) 5-m long flume; a 12.7-m long stainless steel flume; a piston-type, wet-back, force-controlled surface wave generator; a pumping system to create any type of density stratification; and a 3D Particle Tracking Velocimetry (PTV) system. The design and construction of these components along with technical validation and performance tests are presented in this technical note. A scaling analysis demonstrates the suitability of the laboratory to investigate wave-induced current under rotation. The DTP-Lab will pioneer the combined experimental study of surface waves, density stratification and Coriolis forces. The DTP-Lab is presented here with the objective of giving practical information to future users and to describe its novelty and range of applications.